The Cyber Loving Approach: A Model for Mitigating Psychosocial Barriers to Treatment in Type C Hospital Patients in the Digital Era - Indah Datin Nadliroh; Harry Purnomo Salim; Dita Rachmawati (Eduvest - Journal of Universal Studies, 2026)
The development of healthcare services in the digital era requires hospitals not only to improve the quality of medical services but also to pay attention to psychosocial aspects that influence patient satisfaction and loyalty. In Type C hospitals in Indonesia, limited resources and increasing service demands often create psychosocial barriers that may reduce treatment effectiveness and weaken long-term relationships between patients and healthcare providers. This study aims to analyze the influence of service quality dimensions—including technical quality, procedural quality, infrastructural quality, interactional quality, personnel quality, and social support quality—on patient satisfaction and its impact on patient loyalty, with the Cyber Loving Approach as a moderating variable. The research employed a quantitative approach using purposive sampling involving 185 patients from several Type C hospitals in Indonesia. Data were collected through structured questionnaires using a Likert scale and analyzed using Statistical Package for the Social Sciences (SPSS) through validity tests, reliability tests, multiple linear regression, and Moderated Regression Analysis. The results indicate that infrastructural quality, interactional quality, procedural quality, and personnel quality significantly influence patient satisfaction, whereas technical quality and social support quality do not show significant effects. Patient satisfaction was found to have a strong positive influence on patient loyalty. However, the Cyber Loving Approach was not able to significantly moderate the relationship between satisfaction and loyalty. In conclusion, improving service quality—particularly in infrastructure, interaction, service procedures, and staff competence—is essential for increasing patient satisfaction and loyalty in Type C hospitals in the digital era.